This study PERAN RELAWAN TUNA RUNGU DALAM PEMBELAJARAN MEMBACA AL QUR’AN UNTUK ANAK-ANAK BERKEBUTUHAN KHUSUS Studi kasus di TPQ Assakinah Teman Tuli Kota Pekalongan: 1. PENDAHULUAN - Bismillahirrohmanirrohim, Fatkhur Rohman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to explore the role of deaf volunteers in learning to read the Qur'an for children with special needs. by using a qualitative approach with a case study method. This study analyzes the experiences, challenges, and strategies applied by deaf volunteers in teaching the Qur'an packaged in learning at the Assakinah Teman Tuli Al Qur'an Education Park (TPQ Assakinah Teman Tuli). Data were collected through in-depth interviews, participatory observation, and document analysis at an inclusive TPQ involving 10 deaf volunteers and 27 students with special needs. The results of this study show that deaf volunteers play an important role in creating an inclusive and supportive learning environment. They use a variety of innovative methods, such as visual approaches, sign language, and tactile learning tools, to overcome communication barriers and facilitate student understanding. In addition, deaf volunteers show high adaptability and strong empathy, which has a positive impact on student motivation and confidence. Nonetheless, volunteers face a variety of challenges, including limitations in access to appropriate learning resources and the need for more in-depth training in Qur'anic teaching methods. The authors in this regard suggest the need for further support from educational institutions and communities to increase the effectiveness of the role of deaf volunteers, including the development of a more inclusive curriculum and ongoing training. Overall, this study reveals that deaf volunteers have great potential to contribute to learning to read the Qur'an for children with special needs, and emphasizes the importance of collaboration between various parties to realize a more inclusive and accessible education.